Municipalidades na governança das águas: hierarquias e interdependências - Lima, Márcio Junior Teixeira de (2012)
This dissertation addresses the forms of acting of local government in water governance, presenting the case of the Basin Committee Tietê-Jacaré, located in the central region of São Paulo State. The river basin committees are decentralized bodies that aim to discuss and decide the ways in which water resources should be managed at the local level. The new form of governance of water includes several local stakeholders involved in its use, as sectors of civil society and municipalities in the region of the basin. Through a sociological perspective, the main objective is to understand the dynamics of representation and participation of stakeholders within the Basin Committee, focusing on municipal governments. The Committee is understood here as an expression of social space where different agents are present with different social positions and try to impose their world view for all who are present. Therefore, it is important to consider the construction of hierarchies and relations of interdependence involving the main groups active in this space.